Humanizing Addiction Practice Blending Science and Personal Transformation - Douaihy, Antoine (Springer International Publishing, 2018)
This original, eloquent, compassionate, and timely book offers all healthcare practitioners interested and involved in addiction practice a powerful account of an addiction psychiatrist's journey of professional and personal growth, thereby offering readers a unique opportunity to learn deeply from the author's insights, experiences, and struggles in becoming a patient-centered empathic healer. Through sharing and exploring clinical experiences in addiction practice, this fascinating title delves into the lead author and his mentee's personal, professional, and ethical challenges and weaves together science and humanism, offering a wealth of experiential wisdom and tools that have the power to transform our understanding of therapeutic work with people with addictions. Written with empathy and humility, Humanizing Addiction: Blending Science and Personal Transformation provides a compelling argument and framework for integrating humanism with empirically grounded practices. This important book is an invaluable resource for healers from a range of backgrounds: physicians, physician assistants, nurse practitioners, social workers, case managers, patient navigators, clinical and health psychologists, pharmacists, counselors, graduate students, and medical trainees involved in clinical care of people with addiction and substance use problems. .